Composite particle and cosmetic composition
By combining the fine particle size inorganic ultraviolet scattering agent with cellulose nanofibers to form composite particles with high surface area, the problems of precipitation and aggregation of inorganic ultraviolet scattering agents in the prior art are solved, and good uniformity and efficient ultraviolet protection effect of cosmetics are achieved.
Patent Information
- Application Number
- JP2025000773
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-06-17
AI Technical Summary
In the prior art, when using fine-grained titanium oxide as an inorganic ultraviolet scattering agent, it is difficult to effectively inhibit the precipitation and aggregation of titanium oxides, resulting in insufficient UV protection ability, and cosmetics are not easily spread uniformly during application.
Cellulose nanofibers with large quantities of hydrogen bonding points are combined with inorganic ultraviolet scattering agent of fine particle size to form composite particles with high surface area. These composite particles combine with the medium through hydrogen bonding of cellulose nanofibers, improving the stability and uniformity of the particles.
It realizes good dispersion and stability of inorganic ultraviolet scattering agents, improves the uniformity and ultraviolet protection ability of cosmetics during application, and avoids the phenomenon of ultraviolet transmission.
Smart Images

Figure 2025039650000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite particle and a cosmetic composition. [Background technology]
[0002] Conventionally, some cosmetics contain inorganic powders, such as metal powders. These inorganic powders have the property of scattering sunlight. Specifically, when ultraviolet rays contained in sunlight are incident on inorganic powders, they are scattered and blocked from passing through. By including inorganic powders in cosmetics, the cosmetics are provided with an ultraviolet ray blocking effect. For this reason, many cosmetics intended as sunscreens contain inorganic powders.
[0003] Patent Document 1 aims to provide an oil-in-water sunscreen cosmetic that uses inorganic powder such as fine titanium oxide particles to improve the feel when applied, such as stickiness and white cast, while incorporating an inorganic UV scattering agent, and that improves UV protection performance by suppressing precipitation and aggregation of the inorganic UV scattering agent. To solve this problem, the document discloses a technology relating to an oil-in-water sunscreen cosmetic that contains an inorganic UV scattering agent, an anion-modified cellulose nanofiber having an average fiber diameter of 2 to 500 nm, a surfactant, and an oily component.
[0004] However, inorganic powders generally have the property of agglomerating when left alone, and even if a surfactant is added to disperse the powder, the powder will gradually aggregate. This is also true of Patent Document 1, and the technology in question also has insufficient dispersibility of inorganic powder. As a result, the cosmetic product in question does not spread well when applied to the skin, and requires a lot of work, such as multiple reapplications. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2018 / 230228 publication Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide composite particles having inorganic fine particles, which are easily dispersed and spreadable when contained in a cosmetic composition, and a cosmetic composition. [Means for solving the problem]
[0007] The above problem is solved by the following aspects. (First aspect) The present invention comprises aggregated particles in which cellulose nanofibers having an average fiber diameter of 100 nm or less are aggregated together, and a plurality of inorganic fine particles attached to the aggregated particles, The average particle size is 10 μm or less, and the specific surface area is 2 m 2 / g or more, A composite particle characterized by:
[0008] Since cellulose nanofibers have a large number of hydrogen bond points, when the composite particles are mixed with a dispersion medium to prepare a cosmetic, they tend to form hydrogen bonds with each other and become dispersed in the dispersion medium. Furthermore, the cosmetic with dispersed cellulose nanofibers has thixotropy and is easy to spread.
[0009] In addition, cellulose nanofibers form a three-dimensional network in the dispersion liquid and are dispersed with each other, but when the cellulose nanofiber dispersion liquid is concentrated and dried, the cellulose nanofibers aggregate with each other. In particular, cellulose nanofibers with a small average fiber diameter are entangled with each other and aggregated to form aggregated particles. If the average fiber diameter of the cellulose nanofibers is large, they are less entangled with each other, so aggregated particles are less likely to be formed. Since the cellulose nanofibers of this embodiment have an average fiber diameter of 100 nm or less, aggregation is promoted and aggregated particles are easily formed. In addition, the inorganic fine particles attached to the aggregated particles have the effect of suppressing the transmission of ultraviolet rays because they diffusely reflect or scatter sunlight, such as ultraviolet rays. Fine particles generally have the property of aggregating due to the action of intermolecular forces, and the inorganic fine particles are also easily aggregated. However, since the inorganic fine particles are attached to the aggregated particles, their free movement is restricted and they are in a form that is difficult to aggregate with each other.
[0010] It is presumed that some of the inorganic fine particles in this embodiment are attached so as to be embraced by the cellulose nanofibers that form the aggregated particles. A given inorganic fine particle may be embraced by one cellulose nanofiber or may be embraced by multiple cellulose nanofibers. Furthermore, the composite particles formed so as to embrace the inorganic fine particles are composed of cellulose nanofibers that are strongly aggregated by hydrogen bonds with each other, and therefore the aggregation is not easily broken down even when mixed into a medium such as a liquid. Furthermore, the composite particles are difficult to swell in the medium, and are difficult to dissolve or decompose into individual cellulose nanofibers.
[0011] When the average particle size of the composite particles is large, the skin to which the composite particles are applied tends to feel rough. Since the average particle size of the composite particles of this embodiment is 10 μm or less, the skin to which the composite particles are applied is smooth and not easily rough.
[0012] In addition, the specific surface area of the composite particles increases as the number of inorganic fine particles in the composite particles increases, because the surface areas of the inorganic fine particles are added together. In general, when producing a cosmetic product carrying a large amount of inorganic fine particles, a large-sized carrier is used to carry the inorganic fine particles, and the inorganic fine particles are carried on the large-sized carrier. However, in this case, when the cosmetic product carrying the carrier is applied to the skin, it feels rough and causes discomfort.
[0013] In this respect, the composite particles of this embodiment use cellulose nanofibers as the carrier, which allows the carrier itself to have a large surface area despite its small size, and further allows inorganic fine particles to be attached to the carrier, i.e., the cellulose nanofiber, making it possible to further increase the specific surface area of the composite particles. Furthermore, since the surface area of the aggregated particles of cellulose nanofibers is relatively large, a large amount of inorganic fine particles can be attached, and the specific surface area of the composite particles can be increased, resulting in an excellent effect of suppressing the transmission of sunlight. Furthermore, when the composite particles of this embodiment are contained in a medium such as a cosmetic, they are mutually dispersed and easily stretched. The reason for this is unclear, but it is speculated to be due to the effect of the hydrogen bond points and thixotropy of the cellulose nanofibers.
[0014] (Second aspect) The inorganic fine particles are one or more selected from the group consisting of titanium oxide, zinc oxide, iron oxide, and cerium oxide. A composite particle according to a first embodiment.
[0015] Among inorganic fine particles, titanium oxide, zinc oxide, iron oxide, and cerium oxide are excellent in blocking ultraviolet rays.
[0016] (Third aspect) The cellulose nanofibers are at least one of modified cellulose nanofibers in which hydroxy groups of cellulose fibers have been substituted and phosphorus oxo acid ester groups have been introduced, and unmodified cellulose nanofibers in which hydroxy groups of cellulose fibers have not been substituted. A composite particle according to the first or second embodiment.
[0017] The cellulose nanofibers forming the composite particles may be modified or unmodified.
[0018] (Fourth aspect) The primary particle diameter of the inorganic fine particles is 1 μm or less. Composite particles according to any one of the first to third aspects
[0019] In this embodiment, since the inorganic fine particles are equal to or smaller than a predetermined size, the cellulose nanofibers can easily embrace the inorganic fine particles. In addition, the inorganic fine particles attached to the cellulose nanofibers are not easily peeled off.
[0020] In addition, the smaller the inorganic fine particles are, the more they adhere to the aggregated particles, and the more they adhere to the aggregated particles, the more the composite particles can suppress the transmission of sunlight. Furthermore, adhesion of a large amount of inorganic fine particles is preferable because it increases the surface area of the composite particles.
[0021] (Fifth aspect) The inorganic fine particles are contained in an amount of 50% by mass or less. Composite particles according to any one of the first to fourth aspects
[0022] If the amount of inorganic fine particles contained in the composite particles is too large, some of the inorganic fine particles are likely to peel off from the aggregated particles. This peeling phenomenon is undesirable because it leads to aggregation of the inorganic fine particles. In this embodiment, peeling of the inorganic fine particles from the aggregated particles is unlikely to occur.
[0023] Furthermore, when the inorganic fine particles are contained in this amount, the transmission of sunlight can be sufficiently suppressed.
[0024] (Sixth aspect) The inorganic fine particles are hydrophilically treated. Composite particles according to any one of the first to fifth aspects
[0025] The cellulose nanofibers have hydroxyl groups and are highly hydrophilic. The inorganic fine particles have been subjected to a hydrophilic treatment, so they have an affinity with the cellulose nanofibers and are difficult to peel off from the aggregated particles.
[0026] (Seventh aspect) A part of the inorganic fine particles is encapsulated in the aggregated particles. A composite particle according to any one of the first to sixth aspects.
[0027] By including the inorganic fine particles in the aggregated particles, the amount of the inorganic fine particles attached to the aggregated particles becomes relatively large, so that the transmission of sunlight is further suppressed. Also, the inorganic fine particles become less likely to peel off from the aggregated particles.
[0028] (Eighth aspect) A composite particle according to any one of the first to seventh aspects and a thickener, The thickener is one or more selected from the group consisting of polyhydric alcohols, polysaccharides, and water-soluble polymers. A cosmetic composition comprising:
[0029] Since both the thickener and the cellulose nanofibers are hydrophilic, the cellulose nanofibers are less likely to aggregate in the thickener.
[0030] In particular, when the inorganic fine particles are subjected to a hydrophilic treatment, the thickener in this embodiment has hydrophilicity, so that the inorganic fine particles have an affinity for the thickener, and dispersion is promoted together with the aggregated particles. Effect of the Invention
[0031] According to the present invention, composite particles and a cosmetic composition having inorganic fine particles are obtained which are easily dispersible and spreadable when contained in a cosmetic. [Brief description of the drawings]
[0032] [Figure 1] 1 is an SEM image of a composite particle. [Diagram 2]This is an SEM image of inorganic fine particles. [Diagram 3] FIG. 1 shows the results of an interface settling degree test. [Figure 4] FIG. 1 shows the results of an interface settling degree test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] An embodiment of the present invention will be described below. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.
[0034] In conventional cosmetics, metal powder as an inorganic UV scattering agent is mixed with, for example, an aqueous medium, a surfactant, and oil as the main components to produce an oil-in-water cosmetic (Patent Document 1). The metal powder is subjected to a hydrophobic treatment to form micelles with oil, and is dispersed in water. On the other hand, in this embodiment, since the cellulose nanofiber itself has dispersibility, it is not necessary to use an aqueous medium and oil at the same time to disperse the inorganic fine particles, and it is possible to produce a cosmetic composition whose main component is, for example, a hydrophilic component.
[0035] The composite particle and cosmetic composition in this embodiment have aggregated particles in which cellulose nanofibers are aggregated together, and inorganic fine particles attached to the aggregated particles. An image of the composite particle is shown in Figure 1. Figure 1 shows a composite particle 10 in which inorganic fine particles 20 are attached to aggregated cellulose nanofibers 30. The cellulose nanofibers and inorganic fine particles will be described below.
[0036] (Cellulose nanofiber) Cellulose nanofibers have many hydrogen bond points in the cellulose fibers, and when they are mixed with a medium that has an affinity for cellulose nanofibers (for example, water or an organic solvent), they disperse and become a dispersion. In the dispersed cellulose nanofibers, the polar groups in the cellulose nanofibers themselves bond with other cellulose nanofibers through hydrogen bonds or the like, depriving them of freedom and giving them viscosity. When the cellulose nanofibers contain a sufficient amount of the medium, they swell and take on an elongated form, but when the medium content is low, they take on a shrunken form as shown in Figure 1.
[0037] Cellulose nanofibers can be obtained by defibrating (refining) raw pulp, and can be produced by known processing methods such as chemical processing and mechanical processing.
[0038] As the raw material pulp for cellulose nanofibers, one or more of wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fibers, etc., waste paper pulp (DIP) made from brown waste paper, envelope paper, magazine paper, flyer paper, cardboard paper, white waste paper, imitation waste paper, reclaimed waste paper, recycled waste paper, and broke paper, etc., can be selected and used. The above various raw materials may be in the form of a pulverized material called cellulose-based powder, for example. In recent years, the demand for hair styling compositions containing organic ingredients has been increasing, so wood pulp made from broadleaf trees or coniferous trees derived from plants other than waste paper is particularly suitable.
[0039] As the wood pulp, one or more types may be selected and used from chemical pulps such as hardwood kraft pulp (LKP), softwood kraft pulp (NKP), sulfite pulp (SP), dissolving pulp (DP), etc., and mechanical pulp (TMP). In particular, chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), which are wood pulps that increase the cellulose component, are preferred, and bleached pulp (BKP) is suitable.
[0040] As the mechanical pulp, for example, one or more types can be selected and used from stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), chemi-ground pulp (CGP), thermo-ground pulp (TGP), ground pulp (GP), thermo-mechanical pulp (TMP), chemi-thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermo-mechanical pulp (BTMP), etc.
[0041] From the viewpoint of producing cellulose nanofibers of 100 nm or less, it is preferable to use kraft pulp, which is easy to defibrate and has high dispersibility. In particular, since white-based cosmetic compositions tend to be preferred, it is more preferable to use LBKP and NBKP from the viewpoint of improving the high whiteness.
[0042] The cellulose nanofibers may be pretreated prior to defibration. For example, the pretreatment may involve mechanically pre-beating the raw pulp or chemically modifying the raw pulp. There are no particular limitations on the method of pre-beating, and any known method may be used.
[0043] Examples of pretreatment of raw material pulp by chemical techniques include hydrolysis of polysaccharides with acids (e.g., sulfuric acid, etc.) (acid treatment), hydrolysis of polysaccharides with enzymes (enzyme treatment), swelling of polysaccharides with alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (e.g., ozone, etc.) (oxidation treatment), reduction of polysaccharides with a reducing agent (reduction treatment), oxidation with a TEMPO catalyst (oxidation treatment), anionization (anion treatment) and cationization (cation treatment) by phosphate esterification, carbamate formation, etc.
[0044] Examples of the alkali used in the alkali treatment include organic alkali such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide. From the viewpoint of production costs, it is preferable to use sodium hydroxide.
[0045] By subjecting cellulose nanofibers to enzyme treatment, acid treatment, or oxidation treatment, it is possible to reduce the water retention of the cellulose nanofibers, increase the crystallinity, and increase the homogeneity of the cellulose nanofibers. Cellulose nanofibers with low water retention are preferred because they are easier to dehydrate and dry.
[0046] When raw pulp is treated with an enzyme, acid, or oxidation, the amorphous regions of hemicellulose and cellulose contained in the pulp are decomposed, which results in a reduction in the energy required for the pulping process and an improvement in the uniformity and dispersibility of the cellulose fibers. The dispersibility of the cellulose fibers contributes to improving the uniformity of the molded body, for example. However, since the pretreatment reduces the aspect ratio of the cellulose nanofibers, it is preferable to avoid excessive pretreatment.
[0047] Examples of cellulose nanofibers that have been modified by anionization to introduce anionic functional groups include cellulose nanofibers that have been esterified with phosphorus oxoacid, cellulose nanofibers that have been carbamate-modified, and cellulose nanofibers in which the hydroxyl groups on the pyranose rings have been directly oxidized to carboxyl groups.
[0048] Cellulose nanofibers modified by the introduction of anionic functional groups have relatively high dispersibility. This is presumably because the anionic functional groups cause localized charge bias, and these anionic functional groups easily form hydrogen bonds with water and organic solvents in the dispersion.
[0049] When cellulose fibers are subjected to esterification with phosphorus oxoacid, which is an example of anionization, the fiber raw material can be refined, and the cellulose nanofibers produced have a large aspect ratio, excellent strength, and high light transmittance and viscosity. Esterification with phosphorus oxoacid can be performed by the method described in Patent Document 2 (JP Patent Publication No. 2019-199671). An example of cellulose nanofiber (A) in which the hydroxyl groups of cellulose fibers are esterified with phosphorus oxoacid is shown below. A part of the hydroxyl groups of the cellulose fibers is substituted with the functional group shown in the following structural formula (1) and esterified with phosphorus oxoacid, and an example of a cellulose nanofiber in which the amount of the functional group shown in structural formula (1) introduced exceeds 2 mmol per 1 g of cellulose fiber can be given. [Structural formula (1)] [ka] In structural formula (1), a, b, m, and n are natural numbers. At least one of A1, A2,...,An and A' is O, and the rest are R, OR, NHR, or none. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a derivative thereof. α is a cation made of an organic or inorganic substance. This cellulose nanofiber has extremely high light transmittance and viscosity.
[0050] The esterification reaction with phosphorus oxoacids proceeds by adding a solution of less than pH 3.0 containing an additive containing at least one of phosphorus oxoacids and phosphorus oxoacid metal salts to cellulose fibers, heating the fibers, and defibrating the fibers.
[0051] Examples of additives include phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium polyphosphate, lithium dihydrogen phosphate, trilithium phosphate, dilithium hydrogen phosphate, lithium pyrophosphate, lithium polyphosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium polyphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium polyphosphate, phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and phosphorous acid compounds such as pyrophosphorous acid. These additives can be used alone or in combination.
[0052] The cellulose fibers can be defibrated using the following defibration devices and methods. The defibration can be performed by using one or more means selected from homogenizers such as high-pressure homogenizers and high-pressure homogenizers, grinders, grinders, and other mill-type friction machines, refiners such as conical refiners and disk refiners, and various bacteria. However, it is preferable to defibrate the cellulose fibers using a water flow, particularly a high-pressure water flow, and a device or method for finely pulverizing the fibers. This device or method results in very high dimensional uniformity and dispersion uniformity of the resulting cellulose nanofibers. In contrast, for example, when a grinder that grinds between rotating grindstones is used, it is difficult to uniformly finely pulverize the cellulose fibers, and in some cases, there is a risk that some fiber clumps will remain undisintegrated.
[0053] Grinders used to defibrate cellulose fibers include, for example, the Masscolloider manufactured by Masuko Sangyo Co., Ltd. Devices that use high-pressure water flow to pulverize materials include, for example, Starburst (registered trademark) manufactured by Sugino Machine Co., Ltd. and Nanovater (registered trademark) manufactured by Yoshida Kikai Kogyo Co., Ltd. High-speed rotary homogenizers used to defibrate cellulose fibers include the Clearmix-11S manufactured by M Technique Co., Ltd.
[0054] The present inventors have found that when cellulose fibers are defibrated using both a method of grinding between rotating grinding wheels and a method of refining with a high-pressure water jet, and the resulting fibers are observed under a microscope, the fibers obtained using the method of refining with a high-pressure water jet have a more uniform fiber width.
[0055] Defibration using a high-pressure water stream is preferably performed by pressurizing a dispersion of cellulose fibers with a pressure booster to, for example, 30 MPa or more, preferably 100 MPa or more, more preferably 150 MPa or more, and particularly preferably 220 MPa or more (high pressure condition), spraying it from a nozzle with a pore diameter of 50 μm or more, and reducing the pressure so that the pressure difference is, for example, 30 MPa or more, preferably 80 MPa or more, and more preferably 90 MPa or more (reduced pressure condition). The pulp fibers are defibrated by the cleavage phenomenon caused by this pressure difference. If the pressure of the high-pressure condition is low or the pressure difference from the high-pressure condition to the reduced pressure condition is small, the defibration efficiency decreases, and repeated defibration (spraying from the nozzle) becomes necessary to achieve the desired fiber width.
[0056] As a device for defibrating with a high-pressure water flow, it is preferable to use a high-pressure homogenizer. A high-pressure homogenizer is a homogenizer capable of ejecting a slurry of cellulose fibers at a pressure of, for example, 10 MPa or more, preferably 100 MPa or more. When cellulose fibers are treated with a high-pressure homogenizer, collisions between cellulose fibers, pressure differences, microcavitation, etc., occur, and defibration of the cellulose fibers occurs effectively. Therefore, the number of defibration treatments can be reduced, and the production efficiency of cellulose nanofibers can be improved.
[0057] It is preferable to use a high-pressure homogenizer that causes the cellulose fiber slurry to collide in a straight line. Specifically, for example, a high-pressure homogenizer of the counter-collision type (MICROFLUIDIZER (registered trademark), wet jet mill) is used. In this device, two upstream flow paths are formed so that the pressurized cellulose fiber slurry collide in a counter-collision manner at the junction. The cellulose fiber slurry collides at the junction, and the collided cellulose fiber slurry flows out from the downstream flow path. The downstream flow path is provided perpendicular to the upstream flow path, and a T-shaped flow path is formed by the upstream flow path and the downstream flow path. When such a counter-collision type high-pressure homogenizer is used, the energy provided by the high-pressure homogenizer is converted to collision energy to the maximum extent, so that the cellulose fibers can be defibrated more efficiently.
[0058] The cellulose nanofibers obtained by defibration can be dispersed in an aqueous medium to prepare a dispersion liquid prior to mixing with inorganic fine particles. It is particularly preferable that the aqueous medium is entirely water (aqueous solution). However, the aqueous medium may be partially composed of other liquids that are compatible with water. As the other liquids, for example, lower alcohols having 3 or less carbon atoms can be used.
[0059] The cellulose nanofiber of this embodiment can be composed of at least one of modified cellulose nanofibers (hereinafter also referred to as "modified CNF") in which the hydroxy groups of the cellulose fibers have been substituted and phosphorus oxoacid ester groups have been introduced, and unmodified cellulose nanofibers (hereinafter also referred to as "unmodified CNF") in which the hydroxy groups of the cellulose fibers have not been substituted.
[0060] In this embodiment, it is preferable that the aggregated particles contain unmodified CNF. Specifically, it is preferable that the aggregated particles are made of only unmodified CNF, or made of unmodified CNF and modified CNF. In particular, when the aggregated particles are made of unmodified CNF and modified CNF, the ratio of the amount of unmodified CNF to the amount of modified CNF (amount of unmodified CNF: amount of modified CNF) is 99:1 to 1:99, preferably 80:20 to 50:50. The inventors have found that when the aggregated particles are made, unmodified CNF aggregates more firmly with each other and forms particles than modified CNF, and the aggregation is difficult to disintegrate.
[0061] The raw material pulp is preferably defibrated so that the physical properties of the resulting cellulose nanofibers have the desired values or evaluations as shown below.
[0062] <Average fiber diameter> The upper limit of the average fiber diameter of the cellulose nanofiber is 100 nm or less, preferably 90 nm or less, more preferably 80 nm or less, and particularly preferably 70 nm or less. If the average fiber diameter of the cellulose nanofiber exceeds 100 nm, the average particle diameter of the composite particles when made into composite particles is large, and a rough feeling occurs when used as a cosmetic. On the other hand, the average fiber diameter of the cellulose nanofiber (average fiber width; average diameter of single fibers) is not particularly limited, but if it is, for example, 1 nm or more, preferably 2 nm or more, more preferably 3 nm or more, the aspect ratio is relatively large and it is easy to form a structure that easily embraces inorganic particles.
[0063] The average fiber diameter of cellulose nanofibers can be adjusted, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0064] In particular, when the average fiber diameter of the cellulose nanofibers defibrated by esterification with the above-mentioned phosphorus oxoacid is within the above range, the cellulose nanofibers produced have high transparency. When used as a cosmetic, it is preferable to use cellulose nanofibers defibrated by esterification with phosphorus oxoacid from the viewpoint of suppressing white cast.
[0065] The method for measuring the average fiber diameter of cellulose nanofibers is as follows. First, 100 ml of an aqueous dispersion of cellulose nanofibers with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 3,000 to 30,000 times depending on the width of the fibers that constitute it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are arbitrarily drawn. Furthermore, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of the measured values is then taken as the average fiber diameter.
[0066] <Average fiber length> The average fiber length of the cellulose nanofibers (average length of single fibers) is, for example, preferably 0.01 to 500 μm, more preferably 0.5 to 400 μm. If the average fiber length is less than 0.01 μm, the drainage and drying properties are reduced, and it becomes difficult to form a three-dimensional network structure between the cellulose nanofibers. If the average fiber length exceeds 500 μm, the cellulose fibers become more entangled with each other, and the aggregated particles become relatively too large, making it unsuitable for cosmetic compositions.
[0067] The average fiber length can be adjusted as desired by, for example, selecting the raw pulp, pre-treating, defibrating, and the like.
[0068] The average fiber length of cellulose nanofibers is measured in the same manner as for the average fiber diameter, by visually measuring the length of each fiber. The median length of the measured values is taken as the average fiber length.
[0069] <Axle ratio> The axial ratio of the cellulose nanofibers (average fiber length / average fiber width) is preferably 10 to 500,000, more preferably 15 to 400,000, and particularly preferably 20 to 300,000. When the axial ratio of the cellulose nanofibers is less than 10, the cellulose content is almost in a particle shape, making it difficult to form aggregated particles. On the other hand, when the axial ratio exceeds 500,000, the degree of entanglement between the fibers becomes large, making it difficult for the aggregated particles to have the desired average particle size.
[0070] <Crystallization degree> The crystallinity of the cellulose nanofiber is 50 to 100, more preferably 60 to 90, and particularly preferably 65 to 85. If the crystallinity is less than 50, it is difficult to form aggregated particles. If the crystallinity is more than 100, the cellulose nanofiber is insufficiently defibrated, and aggregation is difficult to occur, making it difficult to form aggregated particles.
[0071] The degree of crystallinity is a value measured by X-ray diffraction in accordance with JIS-K0131 (1996) "General Rules for X-ray Diffraction Analysis." Note that cellulose nanofibers have amorphous and crystalline parts, and the degree of crystallinity refers to the proportion of crystalline parts in the entire cellulose nanofiber.
[0072] <Light transmittance> The light transmittance of the cellulose nanofiber (0.2% by mass aqueous dispersion based on solid content) is preferably 5% or more, more preferably 10% or more, and particularly preferably 20% or more. If the light transmittance is less than 5%, when the cellulose nanofiber is used as a cosmetic composition, the cosmetic will have a yellowish hue, and the yellow color will be noticeable when applied to the skin, which is undesirable.
[0073] The light transmittance is the transparency (transmittance of light from 350 to 880 nm) of a 0.2% (w / v) aqueous dispersion of cellulose nanofibers measured using a Spectrophotometer U-2910 (Hitachi, Ltd.). The dispersion medium is purified water.
[0074] <Pseudo particle size distribution> The peak value in the pseudo particle size distribution curve of the cellulose nanofiber is preferably one peak. When there is one peak, the cellulose nanofiber has high uniformity in fiber length and fiber diameter, and inorganic fine particles are easily dispersed. When the cellulose nanofiber has high uniformity in fiber length and fiber diameter, the highly uniform cellulose nanofibers tend to aggregate with each other to form highly uniform aggregated particles. The aggregated particles are in the form of composite particles with inorganic fine particles attached thereto, and are sufficiently dispersed in the cosmetic. Since the inorganic fine particles are also dispersed by the dispersion of the composite particles, the cosmetic containing the composite particles has an excellent effect of suppressing the transmission of sunlight.
[0075] The peak value of the cellulose nanofiber is measured in accordance with ISO-13320 (2009). More specifically, a particle size distribution measuring device (Laser Diffraction / Scattering Particle Size Distribution Meter manufactured by Seishin Enterprise Co., Ltd.) is used to examine the volumetric particle size distribution of the aqueous dispersion of the cellulose nanofiber. The most frequent diameter of the cellulose nanofiber is then measured from this distribution. This most frequent diameter is taken as the peak value. It is preferable that the cellulose nanofiber has a single peak in the pseudo particle size distribution curve measured by the laser diffraction method in the aqueous dispersion state. In this way, the cellulose nanofiber having one peak is preferable because it has been sufficiently refined and can exhibit good physical properties as a cellulose nanofiber. The peak value of the pseudo particle size distribution of the particle size of the cellulose nanofiber having the single peak is, for example, preferably 100 μm or less, more preferably 50 μm or less, and particularly preferably 30 μm or less. If the peak value exceeds 100 μm, the fibers become large, the thixotropy increases, and the shape of the composite particle tends to become non-uniform.
[0076] The peak value in the particle size and the median diameter in the pseudo-particle size distribution of the cellulose nanofibers can be adjusted, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0077] <Viscosity> In the dispersion, the cellulose nanofibers are bonded to each other by hydrogen bonds and the like in a dispersed state, and have viscosity. It is speculated that when shear force is applied to this dispersion, the hydrogen bonds weaken and the viscosity decreases. That is, the cellulose nanofiber has thixotropy. In addition, the viscosity changes depending on the concentration of the cellulose nanofiber contained in the dispersion and the raw material of the cellulose nanofiber. The cellulose nanofiber used in this embodiment has a B-type viscosity of 10 to 300,000 cP, more preferably 100 to 100,000 cP, when the concentration is 1 mass% (w / w). It can be assumed that the aspect ratio of the fiber is also small in the cellulose nanofiber, which results in a decrease in the cohesive force and may make it difficult to form composite particles.
[0078] The B-type viscosity of cellulose nanofiber is a value measured in accordance with JIS-Z8803 (2011) "Method of measuring viscosity of liquids." B-type viscosity is the resistance torque when stirring a dispersion liquid, and the higher the viscosity, the more energy is required for stirring. Measurements were performed at 25°C.
[0079] <Water retention> The water retention of the cellulose nanofiber is, for example, preferably 500% or less, more preferably 300 to 480%. If the water retention exceeds 500%, the water retention of the cellulose nanofiber itself will be high, and the dehydration of the cellulose nanofiber will deteriorate, resulting in composite particles with a high moisture content, which may reduce the cohesive force. There is no particular limit to the lower limit of the water retention of the cellulose nanofiber, but if it is 300% or more, the dispersibility of the cellulose nanofiber will be improved, which is preferable.
[0080] The water retention of cellulose nanofibers can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0081] The water retention of cellulose nanofiber is a value measured in accordance with JAPAN TAPPI No. 26 (2000). <Pulp viscosity> The pulp viscosity of the defibrated cellulose nanofiber is 1 to 10 cps, more preferably 2 to 9 cps, and particularly preferably 3 to 8 cps. The pulp viscosity is the viscosity of the solution obtained after dissolving cellulose in a copper ethylenediamine solution, and a higher pulp viscosity indicates a higher degree of polymerization of cellulose, which also affects the strength of the fiber itself.
[0082] (Inorganic fine particles) Next, inorganic fine particles will be described. The inorganic fine particles are provided in the composite particles for the purpose of suppressing the transmission of sunlight including ultraviolet rays. The content of the inorganic fine particles in the composite particles may be set to 50% by mass or less, preferably 40% by mass or less, and the lower limit may be greater than 0% by mass, preferably 10% by mass or more. If the content exceeds 50% by mass, the ratio of the inorganic fine particles to the aggregated particles is large, and the inorganic fine particles cannot be attached to the aggregated particles. If the content is 10% by mass or more, the effect of suppressing the transmission of sunlight is sufficiently exhibited.
[0083] The upper limit of the primary particle diameter of the inorganic fine particles may be 1 μm or less, preferably 0.9 μm or less, and more preferably 0.8 μm or less. If the primary particle diameter of the inorganic fine particles exceeds 1 μm, the inorganic fine particles are difficult to adhere to the aggregated particles of cellulose nanofibers, or even if they are adhered, they tend to fall off. In addition, the surface area of the composite particles is not sufficiently large. The lower limit of the inorganic fine particles is not particularly limited, but may be 1 nm or more, preferably 3 nm or more, and more preferably 5 nm or more. If the primary particle diameter of the inorganic fine particles is 1 nm or more, the inorganic fine particles will have good dispersibility when put into a medium to make a slurry of the inorganic fine particles. The inorganic fine particles 20 have a nano-sized primary particle diameter, but usually form a lump 40 by adhering to each other due to interactions such as intermolecular forces (see FIG. 2). The primary particles are defined as follows. A secondary particle refers to a primary particle that is aggregated and behaves as a single particle, and a primary particle refers to a basic constituent particle of the substance.
[0084] The primary particle size of the inorganic fine particles was measured by observing the particles under an electron microscope and calculating the average particle size.
[0085] The inorganic fine particles can be used as they are, but it is preferable to subject them to hydrophilic treatment, since they have affinity with cellulose nanofibers and aqueous media. The surface treatment agent used for hydrophilic treatment has the effect of suppressing the surface activity of the inorganic fine particles, improving the dispersibility of the inorganic fine particles, and improving the transparency and squeaking when the inorganic fine particles are contained in a cosmetic. For example, the lower limit of the surface treatment agent may be more than 0 parts by mass, preferably 10 parts by mass or more, and the upper limit may be 50 parts by mass or less, preferably 40 parts by mass or less, relative to 100 parts by mass of the inorganic fine particles.
[0086] The surface treatment agent for the inorganic fine particles is not particularly limited as long as it is dispersible in an aqueous medium, but those containing silicic anhydride and hydrated silicic acid are preferred.
[0087] The shape of the inorganic fine particles is not particularly limited, but examples include spherical, plate-like, spindle-like, needle-like, etc. In particular, when titanium oxide is of the rutile type, it is preferable because it improves the suppression of sunlight transmission in the cosmetic composition.
[0088] The inorganic fine particles are not particularly limited and known inorganic fine particles can be used. From the viewpoint of suppressing the transmission of sunlight, for example, one or more types selected from the group consisting of titanium oxide, zinc oxide, iron oxide, and cerium oxide can be used.
[0089] The shape of the inorganic fine particles used in the composite particles is not particularly limited, but may be, for example, spherical, rod-like, needle-like, spindle-like, plate-like, polygonal, or the like.
[0090] (composite particles) The composite particles of this embodiment have aggregated particles in which cellulose nanofibers having an average fiber diameter of 100 nm or less are aggregated together, and a plurality of inorganic fine particles attached to the aggregated particles, and have an average particle diameter of 10 μm or less and a specific surface area of 2 m 2 / g or more.
[0091] In the case of composite particles, inorganic fine particles may be attached to the surface of aggregated particles or may be encapsulated in aggregated particles. When inorganic fine particles are encapsulated in aggregated particles, the composite particles can have inorganic fine particles not only on the surface but also inside, and contain a large amount of inorganic fine particles, resulting in an excellent effect of suppressing the transmission of sunlight. Here, encapsulation can refer to a state in which a part of the surface of the inorganic fine particles is covered with cellulose nanofibers, or a state in which the inorganic fine particles cannot be observed when the composite particles are observed from the outside because they are covered with cellulose nanofibers.
[0092] <Average particle size> The upper limit of the average particle size of the composite particles is 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less. The lower limit of the average particle size of the composite particles is not particularly limited, but for example, if it is 0.1 μm or more, preferably 1 μm or more, the surface area to which the inorganic fine particles adhere becomes large, which is preferable. If the average particle size exceeds 20 μm, the composite particles tend to cause a rough feeling when used in a cosmetic composition.
[0093] The average particle size of the composite particles was measured in accordance with ISO-13320 (2009). Specifically, the composite particles were dispersed to give a 2% by mass dispersion, and the average particle size was measured in a wet state using a particle size distribution analyzer.
[0094] <Specific surface area> The specific surface area of the composite particles is 2m 2 / g or more, preferably 3m 2 / g or more, more preferably 4m 2 / g or more. 2 If the content is less than 1 / g, the number of inorganic fine particles attached to the composite particles is small, and there is a risk that the transmission of sunlight is not sufficiently suppressed.
[0095] The specific surface area of the composite particles was measured by the BET method using a Quantachrome Instruments NOVA4200e measuring instrument and a nitrogen gas adsorption method.
[0096] The specific surface area of the composite particles was measured in accordance with JIS Z8830:2013.
[0097] The composite particles can be produced by drying using the production method described below, but the moisture content should be 20% by mass or less, preferably 15% by mass or less, and more preferably 10% by mass or less. If the moisture content exceeds 20% by mass, the cellulose nanofibers will not sufficiently aggregate with each other, and the composite particles may deform or adhere to each other to form clumps.
[0098] (Thickener) A thickener can be added to increase the viscosity of the cosmetic, improve the dispersibility of the composite particles, and for the purpose of modification. As the thickener, one or more selected from the group consisting of polyhydric alcohols, polysaccharides, and water-soluble polymers can be used. The mixing ratio of the thickener (thickener:cellulose nanofiber) is 2:1, preferably 3:1, based on the solid content. If the mixing ratio of the thickener to the cellulose nanofiber is too high, it takes a long time to dry, which is not economical. If the mixing ratio is too low, the modification effect cannot be expected.
[0099] Examples of polyhydric alcohols that can be used include, but are not limited to, glycerin, propylene glycol, butylene glycol, pentanediol, dipropylene glycol, hexanediol, heptanediol, etc. Glycerin is particularly preferred from the viewpoints of viscosity increasing properties and dispersibility of composite particles.
[0100] Examples of polysaccharides that can be used include, but are not limited to, quince seed, veegum, xanthan gum, hyaluronate, etc. In particular, hyaluronate is preferred from the viewpoint of thickening properties and dispersibility of composite particles.
[0101] Examples of the water-soluble polymer include, but are not limited to, polyvinyl alcohol, polyvinylpyrrolidone, carboxyvinyl polymer, and polyethylene glycol. In particular, polyvinylpyrrolidone is preferred from the viewpoints of viscosity increase and dispersibility of composite particles.
[0102] (Manufacturing method) Next, a method for producing composite particles will be described. The following production method is an example, and the present invention is not limited to this production method. The method for producing composite particles includes a slurrying step, a mixing and stirring step, and a drying step. The medium described below is water, an organic solvent, or the like.
[0103] <First form> The slurrying step is a step of dispersing inorganic fine particles in a medium to obtain an inorganic fine particle slurry.
[0104] The mixing and stirring process is the process shown below. First, cellulose nanofibers are placed in a medium and dispersed to obtain a cellulose nanofiber dispersion. This cellulose nanofiber dispersion is mixed with an inorganic microparticle slurry and stirred to obtain a mixed liquid. The medium used in the mixing and stirring process may be the same material as the medium used in the slurrying process, or may be a different material.
[0105] In the mixing and stirring step, in addition to the cellulose nanofiber dispersion and the inorganic fine particle slurry, a thickener may be added and mixed and stirred to obtain a mixed liquid.
[0106] The drying step is a step of obtaining composite particles by drying the mixed liquid obtained in the mixing and stirring step with a drying device. The drying device is not particularly limited, and a known device can be used as appropriate. For example, hot air drying, spray drying, air drying, and vacuum drying can be mentioned. Examples of drying devices include air flow drying devices, tunnel drying devices, rotary drying devices with heating tubes, band drying devices, vertical drying devices, ventilation drying devices, rotary drying devices, spray drying devices, drum drying devices, vibration transport drying devices, etc., ventilation drying devices, vacuum box type drying devices, spray drying devices, and stirring drying devices, and one or more of these can be used in combination. Among these, the use of a spray drying device or a spray drying device is preferable because it is possible to uniformly supply heat energy to the material to be dried and to dry it with energy saving.
[0107] The obtained composite particles can be used as a product as it is, or can be crushed and classified to a desired size to be used as a product. Crushing and classifying to a desired size is preferable because it makes the particles finer. Examples of the apparatus used for crushing include impact mills such as hammer mills, media mills such as jet mills and ball mills, homogenizers, pearl mills, and the like.
[0108] <Second form> In the second embodiment of the production method, the slurrying step and the mixing and stirring step out of the three steps of the slurrying step, the mixing and stirring step, and the drying step are carried out in a single step, that is, the slurry mixing and stirring step.
[0109] The slurrying step is a step of dispersing inorganic fine particles in a medium to obtain an inorganic fine particle slurry.
[0110] The slurry mixing and stirring process is a process shown below. First, cellulose nanofibers are placed in a medium and dispersed to obtain a cellulose nanofiber dispersion. Inorganic fine particles are poured into this cellulose nanofiber dispersion, and the mixture is mixed and stirred to obtain a mixed liquid.
[0111] The slurry mixing and stirring process can obtain a mixed solution in one process. However, if the inorganic fine particles have a strong aggregating property, the inorganic fine particles may partially aggregate in the mixed solution. In order to obtain a mixed solution having excellent dispersibility of the inorganic fine particles, the first embodiment of the manufacturing method is more preferable.
[0112] The mixture obtained in the slurry mixing and stirring step is dried in the next drying step to form composite particles. The drying step in the second form is carried out in the same procedure as the drying step in the first form. EXAMPLES
[0113] Examples are shown below. In the following, unmodified cellulose nanofibers refer to "ELLEX (registered trademark)-S", a product of Daio Paper Corporation, and modified cellulose nanofibers refer to "ELLEX (registered trademark)-☆ (Star)", a product of Daio Paper Corporation. <Test Example 1> (1) 100 g of inorganic fine particles (zinc oxide FINEX-50 Sakai Chemical) were dispersed in 900 g of water to obtain an inorganic fine particle slurry having a solid content of 10 mass %. Here, the solid content is the concentration of inorganic fine particles contained in the fine particle slurry. (2) Unmodified cellulose nanofibers were dispersed in water to obtain a 2% by mass unmodified cellulose nanofiber dispersion. 12,000 g of this 2% by mass unmodified cellulose nanofiber dispersion was mixed with 333 g of a thickener (30% by mass glycerin solution) and 800 g of the microparticle slurry of (1) above, and stirred for 30 minutes to obtain a mixed liquid. (3) The mixed liquid obtained above was subjected to a drying process. The drying process is as follows. The mixed liquid was dried using a spray dryer ("TR160" manufactured by PRIS) to obtain composite particles (Test Example 1). The spraying method was a two-fluid nozzle method using two 90-type nozzles. The spray drying conditions were as follows: raw material supply rate 20 kg / h, drying air inlet temperature 200°C, outlet temperature 100°C, spray air pressure 0.6 MPa.
[0114] <Test Example 2> (1) 100 g of inorganic fine particles (zinc oxide FINEX-50 Sakai Chemical) were dispersed in 800 g of water to obtain an inorganic fine particle dispersion. Separately, modified cellulose nanofibers were dispersed in water to obtain a 1 mass% modified cellulose nanofiber dispersion. 100 g of 1 mass% unmodified cellulose nanofiber dispersion was mixed with the total amount (900 g) of the obtained inorganic fine particle dispersion to obtain a fine particle slurry with a solid content concentration of 10.1 mass%. Here, the solid content concentration refers to the total concentration of inorganic fine particles, modified cellulose nanofibers, and unmodified cellulose nanofibers contained in the fine particle slurry. (2) Unmodified cellulose nanofibers were dispersed in water to obtain a 2% by mass dispersion of unmodified cellulose nanofibers. 11,500 g of this 2% by mass dispersion of unmodified cellulose nanofibers were mixed with 333 g of a thickener (30% by mass glycerin solution) and 800 g of the microparticle slurry of (1) above, and stirred for 30 minutes to obtain a mixed liquid. (3) The drying step was the same as the drying step in (3) of <Test Example 1> above. Composite particles (Test Example 2) were obtained by the drying step.
[0115] <Test Example 3> (1) 100 g of inorganic fine particles (zinc oxide FINEX-50 Sakai Chemical) were dispersed in 800 g of water to obtain an inorganic fine particle dispersion. Separately, unmodified cellulose nanofibers were dispersed in water to obtain a 2 mass% unmodified cellulose nanofiber dispersion. 100 g of the 2 mass% unmodified cellulose nanofiber dispersion was mixed with the total amount (900 g) of the obtained inorganic fine particle dispersion to obtain a fine particle slurry with a solid content concentration of 10.2 mass%. Here, the solid content concentration refers to the total concentration of the inorganic fine particles and unmodified cellulose nanofibers contained in the fine particle slurry. (2) Unmodified cellulose nanofibers were dispersed in water to obtain a 2% by mass unmodified cellulose nanofiber dispersion. 11,500 g of this 2% by mass cellulose nanofiber dispersion was mixed with 333 g of a thickener (30% by mass glycerin solution) and 800 g of the microparticle slurry of (1) above, and stirred for 30 minutes to obtain a mixed liquid. (3) The drying step was the same as the drying step in (3) of <Test Example 1> above. Composite particles (Test Example 3) were obtained by the drying step.
[0116] <Test Example 4> (1) 100 g of inorganic fine particles (titanium oxide STR-100N Sakai Chemical) were dispersed in 900 g of water to obtain a fine particle slurry having a solid content of 10.2% by mass. Here, the solid content is the concentration of inorganic fine particles contained in the fine particle slurry. (2) Unmodified cellulose nanofibers were dispersed in water to obtain a 2% by mass unmodified cellulose nanofiber dispersion. 12,000 g of this 2% by mass unmodified cellulose nanofiber dispersion was mixed with 333 g of a thickener (30% by mass glycerin solution) and 800 g of the microparticle slurry of (1) above, and stirred for 30 minutes to obtain a mixed liquid. (3) The drying step was the same as the drying step in (3) of <Test Example 1> above. Composite particles (Test Example 4) were obtained by the drying step.
[0117] <Test Example 5> (1) Unmodified cellulose nanofibers were dispersed in water to obtain a 2% by mass dispersion of unmodified cellulose nanofibers. 12,000 g of this 2% by mass dispersion of unmodified cellulose nanofibers and 333 g of a thickener (30% by mass glycerin solution) were stirred for 30 minutes to obtain a mixed liquid. (2) The drying step was the same as the drying step in (3) of <Test Example 1> above. Composite particles (Test Example 5) were obtained by the drying step.
[0118] <Reference example 6> Reference Example 6 is zinc oxide fine particles. The values shown in Table 1 are measurements for aggregates of zinc oxide fine particles.
[0119] <Reference example 7> Reference Example 7 is fine particles of titanium oxide. The values shown in Table 1 are measurements for aggregates of fine particles of titanium oxide.
[0120] The specific surface area, average particle size, median size, cumulative 10% size, cumulative 90% size, and particle aspect ratio of Test Examples 1 to 5, Reference Examples 6, and Reference Examples 7 are shown in Table 1. The particle aspect ratio is the value obtained by dividing the minor axis diameter of a particle by the major axis diameter of the particle.
[0121] [Table 1]
[0122] (Interface Settling Test) The samples were prepared as follows. (1) In Test Example 1, 2 g of the composite particles was mixed with 38 g of purified water to prepare a 5% by mass dispersion (Test Example 1a). (2) For Test Example 2, 2 g of the composite particles were mixed with 38 g of purified water to prepare a 5 mass % dispersion (Test Example 2a). (3) For Test Example 3, 2 g of the composite particles was mixed with 38 g of purified water to prepare a 5 mass % dispersion (Test Example 3a). (4) For Test Example 4, 2 g of the composite particles was mixed with 38 g of purified water to prepare a 5 mass % dispersion (Test Example 4a). (5) For Test Example 5, 2 g of the composite particles were mixed with 38 g of purified water to prepare a 5% by mass dispersion (Test Example 5a). (6) In Reference Example 6, 2 g of zinc oxide was mixed with 38 g of purified water to prepare a 5% by mass dispersion (Reference Example 6a). (7) In Reference Example 7, 2 g of zinc oxide was mixed with 38 g of purified water to prepare a 5% by mass dispersion (Reference Example 7a).
[0123] For each of Test Examples 1a to 5a, Reference Examples 6a and 7a, 40 mL was placed in a screw cap flask (As One Corporation, capacity 50 mL, mouth inner diameter x body diameter x total length: φ20.3 mm x φ35 mm x 78 mm). After stirring with a magnetic stirrer for 5 minutes at 1200 rpm until uniform, the flask was left to stand at room temperature for 5 minutes and 2.5 hours, and the distance from the water surface to the interface of the composite particles (also called the "sedimentation distance" or "supernatant depth") was measured. The coloring of the dispersion was also evaluated. The results are shown in Table 2, Figure 3 and Figure 4. In the figures, (1a) indicates Test Example 1a, (2a) indicates Test Example 2a, (3a) indicates Test Example 3a, (4a) indicates Test Example 4a, (5a) indicates Test Example 5a, (6a) indicates Reference Example 6a and (7a) indicates Reference Example 7a.
[0124] [Table 2]
[0125] (Consideration) Comparing the sedimentation distance of each sample (Test Examples 1a to 5a, Reference Examples 6a and 7a) after standing for 5 minutes, Test Examples 1a to 5a have a shorter sedimentation distance than Reference Examples 6a and 7a, and are in a dispersed state. For example, in Test Example 1, after standing, the interface 70 settled, and the sample separated into a supernatant liquid 50 and a highly concentrated composite particle dispersion liquid 60, and the sedimentation distance was 5 mm. The sedimentation distances of the other samples were as shown in Table 2. As described above, Test Examples 1a to 5a are in a more dispersed state than Reference Examples 6a and 7a, and are excellent in initial dispersibility. Cosmetics that do not have excellent initial dispersibility require careful kneading or other work when applied to the skin (or body hair), which is time-consuming.
[0126] When comparing the samples after standing for 2 hours and 30 minutes, Test Examples 1a to 5a and Reference Example 6a have shorter sedimentation distances than Reference Example 7a, and are in a dispersed state. For example, in Test Example 1, after standing, the interface 70 settled, and the sample separated into a supernatant 50 and a highly concentrated composite particle dispersion 60, with a sedimentation distance of 18 mm. The other samples also had sedimentation distances as shown in Table 2. Note that, for Test Example 4a after standing for 2 hours and 30 minutes, the composite particles adhered to the inner surface of the screw tube bottle, making it difficult to confirm the interface in FIG. 4, but the inventors confirmed that the particles settled as shown in Table 2. For Test Example 4a after standing for 2 hours and 30 minutes, a curve was added to the figure to clarify the interface 70. The interface 70 refers to the boundary surface between the sample concentrated by standing and the supernatant.
[0127] Regarding the coloring of the dispersion, Test Example 5a exhibited a deep yellow color, and the other samples exhibited white or slightly yellow colors. When used as a cosmetic, if the composite particles are white or slightly yellow, it can be evaluated that there is no significant difference in skin color before and after application to the skin. However, if the composite particles are deep yellow, it can be evaluated that there is a significant difference in skin color before and after application to the skin (or body hair). The parts of the skin (or body hair) where the deep yellow composite particles are applied are visually noticeable, and cosmetics containing such composite particles may be avoided.
[0128] In addition, since Test Examples 1a to 5a contained cellulose nanofibers, they had the thixotropy that is a property of cellulose nanofibers and were easy to spread when applied to the skin (or body hair), whereas Reference Examples 6a and 7a did not contain cellulose nanofibers and were therefore less easy to spread.
[0129] Regarding the average particle size, Test Examples 1a to 4a had composite particles with a size of 10 μm or less, and the skin (body hair) to which these Test Examples were applied was smooth without feeling rough.
[0130] (others) · Unless otherwise specified, the JIS, TAPPI and other tests and measurement methods shown in the above specification are performed at room temperature, especially 25°C, and at atmospheric pressure, especially 1 atm. [Industrial Applicability]
[0131] The composite particles of the present invention can be provided in a known state, for example, in the form of a liquid, emulsion, cream, gel, paste, foam, milk, gel, lotion, wax, grease, skin lotion, beauty serum, etc. Furthermore, the composite particles can be added to cosmetics to provide skin care cosmetics, sunscreen sun care cosmetics, BB creams, makeup cosmetics, and the like. [Explanation of symbols]
[0132] 10 Composite particles 20 Inorganic fine particles 30 Cellulose nanofiber 40 Agglomerates of inorganic fine particles 50 Supernatant 60 Highly concentrated composite particle dispersion 70 Interface
Claims
1. The present invention comprises aggregated particles in which cellulose nanofibers having an average fiber diameter of 100 nm or less are aggregated together, a plurality of inorganic fine particles adhered to the aggregated particles, and a polyhydric alcohol, The cellulose nanofibers are at least one of modified cellulose nanofibers in which hydroxy groups of cellulose fibers have been substituted and phosphorus oxo acid ester groups have been introduced, and unmodified cellulose nanofibers in which hydroxy groups of cellulose fibers have not been substituted; The average particle size is 10 μm or less, and the specific surface area is 2 m 2 / g or more; A composite particle characterized by:
2. The present invention comprises aggregated particles in which cellulose nanofibers having an average fiber diameter of 100 nm or less are aggregated together, and a plurality of inorganic fine particles attached to the aggregated particles, The cellulose nanofibers are made of modified cellulose nanofibers in which at least hydroxy groups of cellulose fibers have been substituted and phosphorus oxo acid ester groups have been introduced, The average particle size is 10 μm or less, and the specific surface area is 2 m 2 / g or more; A composite particle characterized by:
3. The inorganic fine particles are one or more selected from the group consisting of titanium oxide, zinc oxide, iron oxide, and cerium oxide. The composite particle according to claim 1 or 2.
4. The primary particle diameter of the inorganic fine particles is 1 μm or less. The composite particle according to any one of claims 1 to 3.
5. The inorganic fine particles are contained in an amount of 50% by mass or less. The composite particle according to any one of claims 1 to 4.
6. The inorganic fine particles are hydrophilically treated. The composite particle according to any one of claims 1 to 5.
7. A part of the inorganic fine particles is encapsulated in the aggregated particles. The composite particle according to any one of claims 1 to 6.
8. The composite particle according to any one of claims 1 to 7 and a thickener, The thickener is one or more selected from the group consisting of polyhydric alcohols, polysaccharides, and water-soluble polymers. A cosmetic composition comprising:
Citation Information
Patent Citations
Inorganic particle dispersion composition
JP2001049031A
Method for dispersing metal oxide
JP2007505816A
Treated pigment and cosmetic preparation
JP2011037812A
Porous body and manufacturing method thereof, and heat insulation film
JP2015218421A
Resin composition for golf ball and golf ball
JP2017108846A